Acid, pepsin, and mucus secretion in patients with gastric and duodenal ulcer before and after colloidal bismuth subcitrate (De-Nol). Issue 5 (May 1986) - Baron, J H; Barr, J; Batten, J; Sidebotham, R; Spencer, J
Abstract : Basal and pentagastrin stimulated gastric secretion was measured in seven patients with duodenal, and six with gastric ulcers before and after four weeks' treatment with colloidal bismuth subcitrate (as De-Nol), one tablet four times a day. Each duodenal and all but one of the gastric ulcers healed. After De-Nol there were no significant changes in basal, or pentagastrin stimulated volume, acid output, or primary parietal component. There were marked decreases in basal (duodenal ulcer -25%; gastric ulcer -16%) and pentagastrin stimulated total pepsin outputs, (duodenal ulcer -42%, gastric ulcer -36%). There were insignificant decreases in basal output of mucus, but postpentagastrin stimulated mucus output was significantly inhibited (p less than 0.05) in patients with duodenal (-16%) and with gastric ulcer (-27%). The drop in gastric proteolysis after De-Nol is unlikely to be because of the healing of the ulcers and is more likely to be because of the drug. The ulcer healing efficacy of De-Nol may be related to this decline in the proteolytic action of gastric juice, but is unlikely to be because of a quantitative change in mucus, or in acid secretion.